2015
DOI: 10.1086/679519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Status on the Osmoregulation of Green Sturgeon (Acipenser medirostris)

Abstract: Anthropogenic climate change is linked to food web and salinity fluctuations in estuarine environments. Both decreased nutritional status and environmental salinity influence the physiological tolerance and health of fish populations; however, limited information on the interaction of these two factors and their physiological consequences is available. The green sturgeon (Acipenser medirostris) is a species of special concern in California, and the southern distinct population segment is listed as threatened. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 90 publications
2
23
0
Order By: Relevance
“…Additionally, our results are consistent with previous results in juvenile green sturgeon from Haller et al. (), who also found that whole body fat gradually decreased when ration was restricted from 100% optimal feeding rate (OFR) to 25% OFR, but that whole body protein decreased when ration was further restricted to 12.5% OFR. These results, combined with the decline in body weight and condition factor observed in the 0.1% body weight/day treatment, suggest that the low ration had profound effects on the condition of the experimental sturgeon.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, our results are consistent with previous results in juvenile green sturgeon from Haller et al. (), who also found that whole body fat gradually decreased when ration was restricted from 100% optimal feeding rate (OFR) to 25% OFR, but that whole body protein decreased when ration was further restricted to 12.5% OFR. These results, combined with the decline in body weight and condition factor observed in the 0.1% body weight/day treatment, suggest that the low ration had profound effects on the condition of the experimental sturgeon.…”
Section: Discussionsupporting
confidence: 93%
“…Details of rearing practices for green and white sturgeon can be found in Haller et al (2015) and Lee et al (2015), respectively. All handling, care, and experimental procedures were approved by the UC Davis Institutional Animal Care and Use Committee (Protocol #16541).…”
Section: Animal Source and Husbandrymentioning
confidence: 99%
“…Maintenance of good nutritional status is critical because foodlimited fish are more susceptible to predation (Metcalfe et al, 1998;Steele, 2001), disease (Oliva-Teles, 2012), and other environmental factors (e.g., salinity; Haller et al, 2015;Lee et al, 2015). Energy allocation to different molecular and cellular pathways essential to the stress response can be limited in fish with reduced nutritional status (i.e., physiological trade-offs), resulting in decreased stress tolerance (Sokolova, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in phytoplankton and zooplankton communities in conjunction with increasing invasive species richness and abundance has greatly altered food web dynamics in the SFE (Cloern and Jassby ), emphasizing the importance of ecological interactions in understanding global change impacts on SFE native species (Haller et al. ; Lee et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, given that delta smelt actually possess the physiological 'machinery' to cope with conditions outside this range, but cofactors such as energetic costs may play critical roles limiting their performance, it may be beneficial to also focus efforts on other ecological factors (e.g., food resource supply and community structure). Shifts in phytoplankton and zooplankton communities in conjunction with increasing invasive species richness and abundance has greatly altered food web dynamics in the SFE (Cloern and Jassby 2012), emphasizing the importance of ecological interactions in understanding global change impacts on SFE native species (Haller et al 2014;Lee et al 2015). While inclusion of multiple stressors and ecological complexities is challenging, the absence of considering them may lead to ineffective management actions (e.g., population decline despite maintenance of the LSZ zone, due to inadequate food supply or adaptation of marine predators allowing them to expand into LSZ waters).…”
Section: Discussionmentioning
confidence: 99%